Hubungan Service Excellence dan Fasilitas Transportasi Bus dengan Tingkat Kepuasan Konsumen di PT Makmur Halmahera Medan - Br. Sinaga, Ernita Rumenta; Aprinawati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the relationship between service excellence and bus transportation facilities with customer satisfaction levels at PT Makmur Halmahera Medan. The research method used is quantitative with a survey approach. Primary data was obtained by distributing questionnaires to 110 respondents selected using purposive sampling, namely consumers who had used PT Makmur Halmahera Medan bus services at least twice in 2025. Data processing was carried out using SPSS software version 29. The analysis results show that simultaneously, service excellence and bus transportation facilities have a positive and significant effect on customer satisfaction. Partially, service excellence has a significant effect with a beta value of 0.316 (sig. 0.000), while facilities have a more dominant effect with a beta value of 0.417 (sig. 0.000). These two variables together contribute 76.5% to customer satisfaction, while the remaining 23.5% is influenced by other factors outside the scope of this study. These findings emphasize the importance of improving service quality and bus transportation facilities in order to increase customer satisfaction.